Prophets and Profits. A case study of the restructuring of Jewish community schools in Johannesburg - South Africa - Jansen, Jonathan D. (University of Pretoria, 2013)
Thesis (PhD (Education Management and Policy Studies))--University of Pretoria, 2005.